Analisis Sistem Penyimpanan dan Penemuan Kembali Arsip Dinamis pada PT X - Defina Ramadhani; Henry Eryanto; Suherdi Suherdi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
A good archive storage system can be an indicator that a company has done good archive management. If the archive storage system in a company is not well organized, employees will find it difficult to find the documents needed in a short time. The purpose of this research is to find out the storage system used and the steps in storing and finding dynamic archives in one of the companies engaged in insurance. This research uses qualitative methods with data collection techniques through observation, interviews, and documentation, and uses non-probability sampling techniques. The results showed that active dynamic archive storage uses a sequential number storage system. However, some parts use two storage systems depending on the document type. Storing dynamic archives consists of three steps: checking, sorting, and storing. For the step of finding back dynamic archives, there are two ways: manually and digitally. However, no system manages dynamic archives to speed up the retrieval of dynamic archives. For archives that have become inactive archives, they will be submitted to the General Section for further storage at the vendor.